1978
DOI: 10.1128/aem.35.2.329-336.1978
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Polychlorinated Biphenyls on Macromolecular Synthesis by a Heterotrophic Marine Bacterium

Abstract: Growth rates and final cell yields of a polychlorinated biphenyl (PCB)-sensitive pseudomonad isolated from the open ocean were reduced in a dose-dependent manner by 10 to 100 ,ug of Aroclor 1254 per liter, a commercial mixture of PCB isomers added to its culture medium. Effects on growth rates were detected within 1 h (approximately one doubling time) of treatment. By 4 h posttreatment, the amounts of deoxyribonucleic acid and ribonucleic acid per cell in exponentially growing populations treated with subletha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
1993
1993

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The apparent uncoupling of transport and oxidation of selected substrates from growth in the bacteria studied suggested the possibility that PCBs might interfere with the biosynthetic rather than catabolic capacity of sensitive bacteria. Studies of the effect of Aroclor 1254 on macromolecular synthesis in strain 41 are reported in the accompanying manuscript (1).…”
Section: Blakemore and Careymentioning
confidence: 99%
“…The apparent uncoupling of transport and oxidation of selected substrates from growth in the bacteria studied suggested the possibility that PCBs might interfere with the biosynthetic rather than catabolic capacity of sensitive bacteria. Studies of the effect of Aroclor 1254 on macromolecular synthesis in strain 41 are reported in the accompanying manuscript (1).…”
Section: Blakemore and Careymentioning
confidence: 99%
“…Forest Products Laboratory, 1974). Evidence of the in vitro toxicity of individual PAHs and other toxic substances to bacterioplankton has been demonstrated (Calder and Lader, 1976;Blakemore, 1978;Sayler et al, 1982a). However, extrapolation of these data to predict the responses of natural benthic bacterial communities to similar toxicants is questionable.…”
Section: Introductionmentioning
confidence: 99%